Do critical thinkers drink too much alcohol, forget to do class assignments, or cheat on exams? Using a critical thinking measure to predict college students’ real-world outcomes - Franco, Amanda Helena Rodrigues (2017)
Critical thinking is a higher-order way of reasoning composed of the skill and will to use cognitive abilities and knowledge on a daily basis. It is identified as essential by higher education institutions, corporations, and society in general. To analyze whether college students are critical thinkers in their daily lives, the Halpern Critical Thinking Assessment (HCTA; Halpern in Halpern Critical Thinking Assessment (Measurement instrument), Schuhfried, Mödling, 2012) and the real-world outcomes inventory (RWO; Butler in Appl Cogn Psychol 26(5):721–729, 2012) were administered to 238 students. We performed a cluster analysis (K-means-constrained clustering method), and ANOVAs for each cluster solution tested to identify the most suitable clustering solution, taking the RWO inventory dimensions as dependent variables and cluster membership as an independent variable. Four separate clusters emerged, each representing a different profile related to students’ everyday negative outcomes resulting from a lack of critical thinking. We performed multinomial logistic regression to examine which dimensions of the HCTA test, as well as gender, age, and disciplinary area, predicted the four singular groups of students that emerged: “Mature,” “Risk-taking,” “Lost in translation,” and “Reflective.” Results indicate that: (1) age is a relevant predictor of slackness, rashness, and health neglect, all characteristics of “Mature” students; (2) students who are particularly skilled in hypothesis testing tend to be “Risk-taking,” while it is less likely that students who are specifically competent in argument analysis will be in this group; (3) gender is relevant to predict “Lost in translation” students, while argument analysis is negatively related to the chances of being in this group. Our study supports the relevance of critical thinking in daily decisions and everyday outcomes.